Pengaruh Pola Komunikasi Organisasi dan Transparansi Informasi terhadap Kepercayaan Audiens dan Tingkat Keterlibatan di Media Digital TVRI - Manullang, Juniaty; Rahmanita (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2025)
The rapid advancement of information technology has significantly impacted the dynamics of broadcasting media, including public broadcasting institutions such as TVRI. Digital transformation compels public broadcasters to adopt new communication approaches that are not only interactive but also transparent. This study aims to analyze the influence of organizational communication patterns and information transparency on audience trust and engagement on digital platforms. A quantitative approach was used with a survey method involving 20 respondents who are active TVRI digital audience members. The findings reveal that clear communication patterns and good information transparency significantly influence audience trust and engagement. Moreover, information transparency was found to be a more dominant factor than communication patterns in increasing audience engagement. This study provides valuable insights for public broadcasting institutions to design more effective digital communication strategies.